2005
DOI: 10.1523/jneurosci.2356-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Maturation of the Macaque's Lateral Geniculate Nucleus

Abstract: Vision in infant primates is poor, but it is not known which structures in the eye or brain set the main limits to its development. We studied the visual response properties of 348 neurons recorded in the lateral geniculate nucleus (LGN) of macaque monkeys aged 1 week to adult. We measured spatial and temporal frequency tuning curves and contrast responses with drifting achromatic sinusoidal gratings. Even in animals as young as 1 week, the main visual response properties of neurons in the magnocellular (M) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 39 publications
5
54
0
Order By: Relevance
“…Previous studies of connected retinal ganglion cells and LGN neurons have shown that mean firing rates are lower in LGN neurons (Kaplan et al, 1987;Movshon et al, 2005). In our population of 15 cells, the average probability of a retinal ganglion cell spike leading to an LGN spike was 46 Ϯ 16%.…”
Section: Epsp Efficacy and Summation Requirement Of Lgn Action Potentmentioning
confidence: 52%
See 1 more Smart Citation
“…Previous studies of connected retinal ganglion cells and LGN neurons have shown that mean firing rates are lower in LGN neurons (Kaplan et al, 1987;Movshon et al, 2005). In our population of 15 cells, the average probability of a retinal ganglion cell spike leading to an LGN spike was 46 Ϯ 16%.…”
Section: Epsp Efficacy and Summation Requirement Of Lgn Action Potentmentioning
confidence: 52%
“…With 98% of "priming" EPSPs falling within 33 ms of a spike, it appears that an instantaneous firing rate of 30 Hz is needed to bring an LGN neuron to threshold. The summation requirement explains the threshold portion of the function that relates the retinal spike rate to LGN spike rate (Lee et al, 1983;Movshon et al, 2005). This threshold nonlinearity is incorporated as the final stage of most neural models relating synaptic input to spike output (Dayan and Abbott, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…1B). Fourier analyses determined that during recordings most (Ͼ90%) of the contrast stimuli used had a significant amount of energy (Ͼ50%) distributed in the low to medium spatial frequency range (Ͻ10 c/deg), which can effectively drive most LGN neurons under similar lighting conditions such as ours (Derrington and Lennie 1984;Movshon et al 2005). As an example, the contrast responses of a P ON neuron are shown in the form of raster plots (Fig.…”
Section: Visual Stimulus Presentations and Behavioral Tasksmentioning
confidence: 99%
“…Neurons in the LGN of infant monkeys have qualitatively adultlike spatial/temporal response properties as early as 1 wk of age, although retinal development limits the contrast sensitivity and the spatial/temporal resolving power of these neurons (Hawken et al 1997;Movshon et al 2005). However, "ideal observer analyses" indicated that immaturities in the retina or the LGN during the first several weeks of a monkey's life do not entirely account for the reduced spatial vision and therefore additional limits must be imposed by visual cortex Movshon et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, "ideal observer analyses" indicated that immaturities in the retina or the LGN during the first several weeks of a monkey's life do not entirely account for the reduced spatial vision and therefore additional limits must be imposed by visual cortex Movshon et al 2005).…”
Section: Introductionmentioning
confidence: 99%